Estudo da fauna de Hymenoptera parasitóides associados a hortas orgânicas e da utilização de extratos vegetais no controle de Plutella xylostella (Lepidoptera, Plutellidae) - Onody, Helena Carolina (2009)
This work aimed to study the Hymenoptera parasitoids fauna in organic crops areas and the insecticidal activity of plant extracts from Allamanda cathartica (Apocynaceae) and Coriandrum sativum (Apiaceae) and the latex of Euphorbia milii (Euphorbiaceae) on Plutella xylostella (Lepidoptera, Plutellidae). During March 2006 to February 2007 twelve samples were performed using Malaise traps in each of the three studied organic crop areas. Immature Lepidoptera were also collected to verify the emergence of parasitoids. A total of 46,231 specimens, identified in 28 families were collected by Malaise trap. The most representative were Braconidae and Ichneumonidae (Ichneumonoidea), Eulophidae, Mymaridae and Pteromalidae (Chalcidoidea), Scelionidae (Platygastroidea) and Figitidae (Cynipoidea). Twenty-two subfamilies of Braconidae were identified, Microgastrinae being the most abundant in the three locations sampled. Seventeen subfamilies of Ichneumonidae were recognized and, in the three farms, the Campopleginae and Cremastinae were the most abundant. The genera Lysiphlebus, Opius, Dolichozele and Aleiodes were the most abundant of the 81 Braconidae genus identified. The results showed that the practice organic farming has positive effects on the abundance, richness and diversity Hymenoptera parasitoids fauna, but the results varied according to taxonomic level used and the type of management performed. The Braconidae and Ichneumonidae (Ichneumonoidea), Eulophidae and Encyrtidae (Chalcidoidea) were the most important parasitoids reared from the immature Lepidoptera hosts. New information on the associations between hosts and parasitoids were obtained for Hypomicrogaster (Braconidae, Microgastrinae) parasitizing larvae of Hellula phidilealis (Lepidoptera, Pyralidae), Eiphosoma (Cremastinae, Ichneumonidae) parasitizing larvae of Diaphania hyalinata (Pyralidae, Lepidoptera) and Colpotrochia (Ichneumonidae, Metopiinae) parasitizing larvae of Spodoptera eridania (Lepidoptera, Noctuidae). The tests performed with different concentrations of Allamanda cathartica and Coriandrum sativum extracts and Euphorbia milii latex affected the larval Plutella xylostella mortality.